Optical properties of thin films of titanium with transient layers on them - Lendel, V.V.; Lomakina, O.V.; Mel’nychenko, L.Yu.; Shaykevich, I.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Within the Beattie spectroellipsometric method, we measured the ellipsometric
parameters of thin Ті films deposited onto glass substrates by magnetron sputtering in
argon atmosphere. Measurements were carried out at five angles of incidence with light
from the visible and ultraviolet ranges of the spectrum. Using the Airy recurrent
formulas, we solved the inverse problem of ellipsometry for a three-layer model of films.
The model includes nine unknown quantities – three thicknesses of layers and six optical
constants, namely: the refractive and absorption indices of all these layers. The results
obtained show that the upper layer being in contact with air consists of titanium oxide of
the TiO₂ type, the second layer is made of pure metallic titanium, and, finally, the third
layer adjoining the glass substrate is also oxide TiO₂. It is worth noting that the optical
constants of the second layer are practically identical to those of massive Ті. The
calculations of the film thicknesses and optical constants by using the one-layer model
gave the values significantly different from the optical constants of massive titanium. In
addition, the studies of both the electric conductance of the prepared Ті films and
morphology of their surface with an atomic force microscope were carried out.